Muslim Bengal writes back: A study of Rokeya’s representation of Europe - Hasan, Md. Mahmudul (2012)
Rokeya Sakhawat Hossain (1880 – 1932) is the most prominent Muslim feminist writer from what is now Bangladesh and has huge posthumous public influence in the entire Muslim Bengal. During the time of her active creative career, British colonialism was at its height in India. British India was a confluence of Indian and European people and both the groups interacted with each other, albeit maintaining some distance given the prevailing colonial relations between them. As Muslims felt doubly dispossessed and subordinated by the colonial powers, compared to other religious communities, their engagement and interaction with the Europeans living in India at that time was minimum. However, although she experienced the obtrusive presence of colonial administrators and intellectuals in her country, she had the privilege of interacting with English people who were her civil servant husband’s colleagues in the bureaucracy even though the scope of the communication was restricted by the Indian notion of purdah and by the colonizer’s culture of maintaining distance from the colonized. Nevertheless, both the availability of English literary works and her familiarity with the British expatriates brought her in contact with European culture. From passing comments on European – especially British – society in her oeuvre, she moved on to interpretatively translate Marie Corelli’s The Murder of Delicia (1896) and creatively transformed its message to locate commonalities in women’s plight in England and in Muslim Bengal. Although Rokeya’s husband Sakhawat Hossain studied in England and many of her male, Hindu contemporary writers traveled to the metropolis, Rokeya never visited Europe. So her representation of Europe was mainly imaginary. In this study, I will discuss Rokeya’s imagined Europe and how she establishes a commonality between women of Muslim Bengal and those from England in order to dispel the widely-held perception that, unlike Muslim women, European women are fully empowered. Rokeya argues that women in both societies are subjugated by patriarchal power and thus she demystifies the presumed superiority of European women over their Muslim sisters in Bengal.